OPTIMALISASI TEKNOLOGI PENDIDIKAN: PELATIHAN PEMBUATAN VIDEO PEMBELAJARAN UNTUK GURU DI PULAU LENGUDI - Endra, Robby Yuli; Redaputri, Appin Purisky; Aprinisa, Aprinisa; Santoso, Niki Agus; Rizkyna, Shanaz (Politeknik Perkeretaapian Indonesia Madiun, 2025)
The training on making educational videos on Lengudi Island, which was held from 6-8 August 2024, aims to improve teacher competence in utilizing technology for learning. Based on an initial survey, the majority of teachers have limitations in using technology. This training program involves theory and direct practice, including video planning, production, and editing. The results of the training showed an average increase in teacher skills of 45% based on the pre-test and post-test. In addition, 10 educational videos produced by participants were considered creative, relevant, and in accordance with the curriculum. The main challenges include limited devices and internet access. This training has been shown to improve teacher skills and have a positive impact on the quality of student learning. Recommendations include further training and improving educational infrastructure.